Conjugation of functionalized gadolinium metallofullerenes with IL-13 peptides for targeting and imaging glial tumors. (April 2011) - Fillmore, Helen L; Shultz, Michael D; Henderson, Scott C; Cooper, Patricia; Broaddus, William C; Chen, Zhi Jian; Shu, Chun-Ying; Zhang, Jianfei; Ge, Jiechao; Dorn, Harry C; Corwin, Frank; Hirsch, Jerry I; et al.
Background: Glioblastoma multiforme is the most common and most lethal primary brain tumor in humans, with median survival of approximately 1 year. Owing to the ability of glioma cells to aggressively infiltrate normal brain tissue and survive exposure to current adjuvant therapies, there is a great need for specific targeted nanoplatforms capable of delivering both therapeutic and imaging agents directly to invasive tumor cells.Method: Gadolinium-containing endohedral fullerenes, highly efficient contrast agents for MRI, were functionalized and conjugated with a tumor-specific peptide and assessed for their ability to bind to glioma cells in vitro .Results: We report the successful conjugation of the carboxyl functionalized metallofullerene Gd3 N@C80 (OH)-26 (CH2 CH2 COOH)-16 to IL-13 peptides and the successful targeting ability towards brain tumor cells that overexpress the IL-13 receptor (IL-13Rαα2).Conclusion: These studies demonstrate that IL-13 peptide-conjugated gadolinium metallofullerenes could serve as a platform to deliver imaging and therapeutic agents to tumor cells.